Use of Synonymous in The Qur'an (Semantic Analysis Study) - Al Sayyid, Abdul Rahman; Habibi, Muhammad Yusuf; Arief, Ahmad Fahmy; Husin, Saifudin Ahmad (Jurnal Al-Maqoyis, 2023)
In the use of language, sometimes we find a difference between one speech and another speech with expressions that have one meaning. This phenomenon is also called by linguists with synonyms. Synonyms are two words that have one or more meanings, such as "death" and "died". This research aims to: 1. know the analysis of the word forms that are synonymous in Surah Al-Baqarah, 2. Analyze the meaning of rich words that are synonymous in Surah Al-Baqarah. The type of research used in this research is literature research with a qualitative approach. The primary data used are verses containing synonymous words in surah Al-Baqarah. And this research uses content analysis with the krippendorf data analysis model. The results of this research are: there are three forms of synonymous words which include: 1. synonyms inletter form , 2. synonyms in formname, and synonyms in the formfi'il. Adapum means 1. for synonyms inletter formamong them said  "from"can meanli ibtida ghayyah (to begin the purpose), li tab'idh (part),liziyadatil taukid(for amplifier), while the word "on  " can meanthat of (Because), min (from) 2. Tosynonyms in formnameamong them the words "the other daywhich is used to mention the end of world life, while the wordDoomsdayused for the mention of after the end of life in the world, and 3. Forsynonyms in formfi'il for example saidcreationwhich is used for the creation from nothing to exist, while the wordmake  used from there then made into something new. In this study there is something new in that the division of synonym forms is different from the usual types of synonyms, namely: the synonym form consists of isim, fi'il, and letters while the synonym type consists ofat-taraduf al kamil, syibhut taraduf, at-taqaruf ad-dalali, at-tafawuf (fil 'umum, fil special, fil quwwah, Fil malamih)